Peningkatan Kualitas Sumber Daya Manusia dalam Pelaksanaan Pemilihan Kepala Desa melalui Implementasi Sistem E-Administrasi: Improving the Quality of Human Resources in the Implementation of Village Head Elections through the Implementation of the E-Administration System - Mulyadi, Dedi; Suheri, Agus; Nurpandi, Finsa; Utami, Tanti Kirana; Kuswandi, Kuswandi; Nur, Himan; Mulyana, Aji; Triyana, Putri; Susilawati, Eli; Rizal, Desca Mochamad; Nurmariam, Yuli; Permatasari, Ira; Yudiansyah, Fakhrian (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The general election (Pemilu) is a process by which people elect individuals to political positions at various levels in Indonesia. Elections are conducted to elect leaders such as presidents or executive officials, representatives of the people in the legislature, and village heads. A quality election will certainly give birth to quality leaders as well. The Village Head as a leader at the village level will represent the quality of a village. Thus, the function of the Village Head towards village development is to think, plan, and implement. One of the efforts made by the Cianjur Regency Government to improve the quality of the implementation of the simultaneous village elections is by creating an E-Administration system to be used in the registration process for candidates for village heads. The purpose of creating this E-Administration system is to facilitate the organizers and prospective village head candidates in the implementation of registration The implementation method in this service activity goes through several preparatory stages, namely First, increasing commitment. Second, development and harmonization of the e-administration system prototype. Third, supervision of the legalization process. And fourth, mentoring/technology transfer of the e-administration system. The results of this research are the formation of an E-Administration system designed by the IT Team of the Faculty of Engineering, Suryakancana University, which is adaptive to existing systems in stakeholders or institutions.